2019
DOI: 10.1111/ppa.12985
|View full text |Cite
|
Sign up to set email alerts
|

Phenotyping Kariega × Avocet S doubled haploid lines containing individual and combined adult plant stripe rust resistance loci

Abstract: The bread wheat cultivar Kariega has maintained its stripe rust resistance since the first detection of Puccinia striiformis f. sp. tritici (Pst) in South Africa during 1996. Doubled haploid mapping population (MP) lines derived from a Kariega 9 Avocet S cross, carrying consistently detected adult plant resistance (APR) quantitative trait loci (QTLs)/gene combinations, were phenotyped at macroscopic and microscopic levels. Field data obtained over four seasons revealed that MP lines carrying a combination of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…Despite the many reports proposing gene combinations as a resistance breeding strategy, few studies have actually investigated complementary effects of gene combinations at the histological level. In an analysis of stripe rust histopathology in the spring, wheat cultivar Kariega, Maree et al [46] have shown that colony length, number of haustorial mother cells and HI all verified high levels of resistance in lines with three resistance QTL. Although most lines with two QTL showed acceptable levels of resistance, the stripe rust phenotype seemed to be influenced by the particular QTL combination [46].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the many reports proposing gene combinations as a resistance breeding strategy, few studies have actually investigated complementary effects of gene combinations at the histological level. In an analysis of stripe rust histopathology in the spring, wheat cultivar Kariega, Maree et al [46] have shown that colony length, number of haustorial mother cells and HI all verified high levels of resistance in lines with three resistance QTL. Although most lines with two QTL showed acceptable levels of resistance, the stripe rust phenotype seemed to be influenced by the particular QTL combination [46].…”
Section: Discussionmentioning
confidence: 99%
“…The variety Kariega reportedly contains three Yr APR genes/QTL that in combination provide complete resistance (Maree et al. 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Stripe rust inoculations at seedling and adult plant stages were performed with urediniospores of the South African Pst pathotype 6E22A+ (virulent to Yr2 , Yr6 , Yr7 , Yr8 , Yr17 , Yr25 and YrA ; avirulent to Yr1 , Yr3a , Yr4a , Yr4b , Yr5 , Yr9 , Yr10 , Yr15 and Yr27 ) 56 and pathotype 30E142A+ 16 (virulent to Yr2 , Yr3a , Yr4a , Yr6 , Yr7 , Yr8 , Yr9 , Yr19 , Yr25 , Yr27 and YrA; avirulent to Yr1 , Yr4b , Yr5 , Yr10 , Yr15 , Yr24 , Yr32 , YrCle , YrMor , YrSd , YrSp , YrSu and YrHVII) . In brief, freshly propagated urediniospores were suspended in FC-43 oil (3M Fluorinert FC-43) and then sprayed onto the leaves using a high-pressure air sprayer.…”
Section: Methodsmentioning
confidence: 99%